Identifying the optimal FSW process parameters for maximizing the tensile strength of friction stir welded AISI 316L butt joints. (April 2019) - Shashi Kumar, S.; Murugan, N.; Ramachandran, K.K.
Highlights: AISI 316L austenitic stainless steel is successfully joined using the FSW process. Regression model is developed to predict the tensile strength of the joints. The regression model is verified for adequacy using statistical tests. The tensile strength of the joints is correlated to the microstructural features. Nonlinear optimization method is used for maximizing tensile strength of the joints. Abstract: AISI 316L stainless steel sheets were friction stir welded in the butt joint configuration as per the design of experiment (DoE) developed using the response surface method; Box Benkhen design. The primary friction stir welding (FSW) process parameters; tool spindle speed, tool transverse speed, downward force and tool tilt angle were considered as factors of the experiment. A response surface (second order) regression model for the response, ultimate tensile strength (UTS) of the joints as a function of tool spindle speed, tool transverse speed, downward force and tool tilt angle was developed. Statistical tests such as ANOVA, F- ratio and values of actual and adjusted R 2 were used to verify the adequacy of the developed model and the model was validated using conformity experimental trials. The analysis of the model showed that the UTS of the joint is sensitive to all the primary FSW parameters. Also, the tool spindle speed, tool traverse speed and downward force have significant interaction effect on the UTS of the joints. The non-linear optimization of the FSW process yielded 604 MPa as optimal UTS corresponding to optimal tool spindle speed of 597 rev/min, tool traverse speed of 74 mm/min, downward force of 13 kN and tool tilt of 1.5°.